How well ultrasonic waves penetrate glass, SS, and plastics? - Nguyen Van Kien; Young Han Jeong; Sunghwan Kim; Jae Jeong Ryoo (Ultrasonics Sonochemistry)
To effectively utilize ultrasound, it is crucial to identify materials and media that facilitate optimal penetration. Extraction and aluminum foil erosion experiments were performed using beakers made of glass, stainless steel, and various plastics (PE, PFA, and PTFE) under different ultrasonic conditions. Additionally, ultrasound-assisted chromatography was conducted in six solutions with varying surface tensions: water, alcohol, 6% and 17% NaOH, and 20% and 35% sucrose in water. The results of the extraction and erosion experiments indicated that glass demonstrated the highest extraction efficiency and the strongest physical effects, with minimal ultrasound energy attenuation, particularly under sweep mode and low-frequency conditions. In chromatography, the findings showed that ultrasound transmission was more effective in a 6% NaOH aqueous solution compared to water.